Asthma: shift some indicators proteinase-inhibitory system in the lungs of guinea pigs and their correction of thiotriazolin. - Kolishetska, M. A.; Vesklyarova, U. P.; Zastryzhna, M. L. (Journal of Education, Health and Sport, 2017)
The research results show that under the conditions of this experimental asthma is a violation of the functional state of proteinase-inhibitory system, which is manifested by excessive activation proteyinaz potential. Reported increase level of azoalbumin, azokazeyin and azokolahen, especially on the 33rd day of the experiment and depression protease inhibitors. This leads to the development of protease-inhibition imbalance, including breach of cellular homeostasis in general. Application of thiotriazoline showed its corrective effect on the performance changed proteolysis, a significant increase in inhibitory protect the lungs of guinea pigs in the conditions of experimental asthma.